Kerangka Pemahaman Hadis Hasbi Ash-Shiddieqy: Antara Tekstual dan Kontekstual - Hedhri Nadhiran; Sofia Hayati (Fakultas Ushuluddin dan Pemikiran Islam Universitas Islam Negeri Raden Fatah Palembang, 2022)
The Problem arises related to hadith is how to search the ideal understanding so that the source of this religion remains relevant and its content can be practiced. History records that the typology of hadith understanding that dominates almost throughout history is textual understanding. In the modern era, this typology has crystallized more and more resulting in the standardization of Islamic religion (orthodoxy) which sometimes seems out of date. This condition is exacerbated by the widespread understanding of several groups of Islamic movements that support and practice fanaticism and radicalism, where in understanding hadith, they tend to be hard textual and it seems easy to brand heresy, even infidels towards other groups so that in the Indonesian context, it can threaten the disintegration of the nation. This is where Hasbi's contribution - as a reformer figure, offers an understanding of hadith by paying attention to the aspect of the spirit or soul of the Shari'a, especially for muamalah traditions. Hasbi's offer seems to be an 'alternative' understanding of hadith which is more moderate and in accordance with the Indonesian condition.